On the action patterns of cyclodextrin glucanotransferases - Varuzhan H. Abelyan (ՀՀ ԳԱԱ հրատ.)
The action patterns of various cyclodextrin glucanotransferases (CGTase)from different groups of microorganisms have been studied.
Keywords: Biology; Microbiology